Progression of myopia in children and teenagers: a nationwide longitudinal study - Tricard, Dorian; Marillet, Simon; Ingrand, Pierre; Bullimore, Mark A; Bourne, Rupert R A; Leveziel, Nicolas (British journal of ophthalmology, 2022)
BackgroundData on myopia prevalence and progression in European children are sparse. The aim of this work was to evaluate the progression of myopia in children and teenagers in a large prospective study.MethodsA prospective study involving a nationwide cohort. Myopia was defined as a spherical equivalent (SE) of ≤ –0.50 diopters (D). Data on refractive error, gender and age were collected in 696 optical centres in France between 2013 and 2019, including 136 333 children (4–17 years old) in the analysis.Progression of myopia was assessed between the first visit and the last visit over up to 6.5 years.ResultsMean age was 11.3±3.8 years (55.0% of female). The proportion of children progressing more than –0.50 D per year was higher in age groups 7–9 years and 10–12 years and in children with SE ≤ –4.00 D at first visit, representing 33.1%, 29.4% and 30.0% of these groups, respectively. In multivariate analysis, progression during the first 11–24 months was higher in the 7–9 and 10–12 age groups (–0.43 D and –0.42 D, respectively), for higher SE at baseline (at least –0.33 D for SE ≤ –1 D) and for girls (–0.35 D).ConclusionThis is the first French epidemiological study to investigate myopia progression in a large-scale cohort of children. Sex, age groups and myopia severity are associated with differing rates of progression.